Investigation of Dynamic Thiol/Disulfide Homeostasis and Nitrosative Stress in Patients with Wilson Disease - Yücel, Emine Melis; Konduk, Bugra Tolga; Saracaloglu, Ahmet; Barutçu, Sezgin; Demiryürek, Seniz; Kaba, Fatma; Güngen, Belma Dogan; Demiryürek, Abdullah Tuncay (Turkish Journal of Gastroenterology, 2021)
Background: Wilson disease (WD) is an autosomal recessive inherited disorder of copper (Cu2+) metabolism, resulting in Cu2+ accumulationand liver and central nervous system toxicity. Oxidative stress may have a role in the pathogenesis of Wilson disease, but the rolesof thiol/disulfide homeostasis and nitrosative stress have not been examined. The purpose of this study was to evaluate whether thereis a modification in thiol/disulfide homeostasis and nitrosative stress in patients with Wilson disease.Methods: A total of 50 patients with Wilson disease (42 under drug treatment and 8 newly diagnosed patients with no drug treatment)and 50 healthy gender- and age-matched controls were enrolled for this study. Serum native thiol and total thiol levels were measuredwith a spectrophotometric method. The number of disulfide bonds and the related ratios were determined from these measurements.Serum nitric oxide (NO) and 3-nitrotyrosine (3-NT) levels were analyzed using chemiluminescence and ELISA assays, respectively.Results: The average native thiol levels of the patient group under drug treatment were found to be markedly higher than the levels ofcontrols (P < .05). We detected no marked changes in total thiol and disulfide levels, and disulfide/total thiol, disulfide/native thiol, ornative thiol/total thiol ratios between groups. We found significant elevations in NO levels in Wilson disease group before drug treatment,and the 3-NT levels in the Wilson disease groups prior to (P < .05) and under drug treatment (P < .01), when compared to controls.Conclusion: Our data are the first to show that nitrosative stress and thiol/disulfide homeostasis can contribute to the pathogenesis ofWilson disease.